A new genus and new species of Neotropical Cerambycinae (Coleoptera, Cerambycidae) - Bezark, Larry G.; Santos-Silva, Antonio (Zootaxa, 2022)
One new genus and three species are described and illustrated: Sulcogracilia mexicana new genus and species from Nuevo León, Mexico (Graciliini); Methia nigra sp. nov. from Quetzaltenango, Guatemala (Methiini) and Euderces lineatus from the State of Mexico, in Mexico (Tillomorphini). The new species of Euderces is included in a previous key.